AREAS OF THE PRECAMBRIAN TECTONO-MAGMATIC ACTIVIZATION OF THE EASTEUROPEAN PLATFORM BASEMENT - SVESHNIKOV, K.; SIVORONOV, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Since Mezoproterozoic age the Ukrainian shield was subjected to processes of the: 1) reflected (magmatic I-type associations), 2) independent (A-type associations) and 3) linear tectono-magmatic activization (granophyre granite association). 1-st stage was connected with transformation of geoblocks system existed in the Early Precambrian into one complete structure – the platform basement. 2-nd stage, most likely, was connected to growth of the arch-raising in the Western part of the platform. 3-rd stage was connected to processes in the transcontinental Ochotsko-Baltic lineament and with processes which took place in the Sveconorvegian geoblock.